Genetic Analysis of Mate Discrimination in Drosophila simulans - Chu, Y. (2013)
Courtship is an elaborate behavior that conveys information about the identity of animal species and suitability of individual males as mates. In Drosophila, there is extensive evidence that females are capable of evaluating and comparing male courtships, and accepting or rejecting males as mates. These relatively simple responses minimize random sexual encounters involving subpar conspecific males and heterospecific males, and over generations can potentially select novel physical and behavioral traits. Despite its evolutionary and behavioral significance, little is still known about the genes involved in mating choice and how choices for novel males and females arise during evolution. D. simulans and D. sechellia are two recently diverged species of Drosophila in which females have a preference for conspecific males. Here we analyzed a total of 1,748 F2 hybrid females between these two species and found a small number of dominant genes controlling the preference for D. simulans males. We also mapped two redundant X-linked loci of mating choice, Macho-XA and Macho-XB, and show that neither one is required for female attractiveness. Together, our results reveal part of the genetic architecture that allows D. simulans females to recognize, mate and successfully generate progenies with D. simulans males.